Strengthening the Character Education of Nature School ‎Students Through the Learning with Nature Program - Sholeh, Muhammad; Syahrial; Supian; Sofwan, Muhammad; Vahlepi, Sahrizal; Alirmansyah (JPI: Jurnal Pustaka Indonesia, 2026)
Character education plays a central role in Indonesia's national education system, yet holistic approaches that integrate values through direct, nature-based experiences remain underexplored. This study aims to analyze how the Belajar Bersama Alam (Learning with Nature) program at two nature-based schools in Jambi Province strengthens character education holistically. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observation, and document review involving 12 participants from Sekolah Alam Muaro Bungo and Madrasah Alam Insan Rabbani Sungai Penuh. Purposive sampling was applied to select school principals, classroom teachers, students, and parents. Data were analyzed using Miles, Huberman, and Saldaña's interactive model, with triangulation to ensure validity. Results indicate that the program effectively develops all four dimensions of Ki Hadjar Dewantara's character framework, Olah Hati, Olah Pikir, Olah Rasa, and Olah Raga, supported by teacher exemplary conduct, a character curriculum comprising 70% Akhlakul Karimah content, and active school-family-community partnerships. This study contributes an empirical model of contextual, nature-based character education in Indonesia, demonstrating that academic achievement and character development can be achieved synergistically.